Frequency and Determinants of Breastfeeding in Greece: A Prospective Cohort Study during the COVID-19 Pandemic - Maria Tigka; Dimitra Metallinou; Christina Nanou; Zoi Iliodromiti; Katerina Lykeridou (MDPI AG, 2022)
Breastfeeding is considered to be the cornerstone of child health. In Europe however, overall breastfeeding rates remain low. The present study aimed at estimating the frequency of breastfeeding in Greece during the COVID-19 pandemic period and comparing findings with the latest national study in order to identify a potential impact of the pandemic. Additionally, possible correlations of socio-cultural and demographic characteristics with breastfeeding indicators were investigated. This prospective cohort study included 847 women from five tertiary maternity hospitals, between January and December 2020. Data were collected by a structured questionnaire via interview during hospitalization and via telephone in the first, third and sixth month postpartum. Results showed that all breastfeeding indicators improved over the last three years. Full breastfeeding reached 7.2%, contrary to 0.78% of the latest national study at six months postpartum. Employment, marital status, educational level, mode of delivery, type of maternity hospital, body mass index before pregnancy, previous breastfeeding experience of the mother and infant's birth weight correlated significantly with breastfeeding indicators at different time periods. The COVID-19 pandemic seems to have favorably influenced breastfeeding initiation and duration in Greece due to lockdowns, home confinement and teleworking.